Genetics of morphinane alkaloids in opium poppy (Papaver somniferum) - SHUKLA, SUDHIR; KHANNA, K R; SINGH, S P (The Indian Journal of Agricultural Sciences, 2013)
An experiment was carried out during winter season of 1990--91 on additive-dominance model for 2crosses ('NBRI 1'x'BR 222' and 'NBRI 2'x'BR 222') to study !.he gene actions involved in the inheritance of morphinane alkaloids (mophine, codeine and thebaine) in opium poppy (Papaver somniferum L.). Non-significant chi-square (X2) showed the validity of additive-dominance model. Dominance (h) effectwas higher than additive (d) effect. Digenic interactions indicated the prevalence of additive X additive (f) gene. effect for morphine and dominance x dominance (f) for codeine and thebaine in both the crosses. The sign of dominance (h) and dominance X dominance (f) indicated duplicate gene action for all the morphinane alkaloids. Recurrent selection involving desired recombinants may be utilized to improve the alkaloids.